Formação de formadores como agentes de transformação - Macambira, Daniela Miranda da Costa (2014)
This research is inserted in the field of Applied Linguistics and has the general objective to understand critically how the activities of a project about continuing formation of teachers and coordinators collaborate to produce meanings about reading and writing of the subjects involved in the process. It is inserted in the research group LACE (Language Activities in the School Context - PUC - SP), which focuses mainly on the training of critical-reflexive educators and students and includes critical and collaborative research that investigates the constitution of the subjects, their forms of participation and the production of senses and meanings in education (LIBERALI 2012). This study is grounded in the Theory of Socio-Historical-Cultural Activity (Vygotsky, 1934/1993, LEONTIEV, 1959/1988, Engestrom, 2000/2005), when it understands the subjects historically, constituting themselves and others through mediated relationships with the world (LIBERALI , 2012), in the concept of Creative Chain (LIBERALI, 2006) that becomes central in the search and transformation of critical professionals, in the constitution of the reflective professional based on the language (Bakhtin, 1953/2003) and inside the role of collaboration in teacher education (Magalhães, 2009). Therefore, the research is structured as a Critical Research of Collaboration (Magalhães, 2009), which enables the search for transformation of all involved. The focus of this study resided in critical knowledge and in the process of becoming subject of your own action. The research was conducted through a set of activities, namely: a) the study of videotaped encounters between planning coordinators of Aprender Editora (Publisher Learn), and b) the videotaped meetings of studies about the planning of the coordinators and educators of the publisher. The participants in this research are the professionals of a pedagogical support team which is responsible for the continuing formation project, which is developed with educators, coordinators and teachers, currently developed in 87 cities situated in the state of Ceara. Some data were produced in 2012 and others in 2013. To critically understand the activities that make the project for continuous formation, the language will be understood and analyzed as constitutive in a collaborative process. Data were analyzed based on categories that seek to realize the production of knowledge in argumentation and in verbal interactions considering the enunciative, discursive and linguistic contexts (Liberali, 2006-2012-2013). Therefore, the research was consisted of the analysis on the Aprender Editora Project of Formation, called Project Reading You Get to Knowing. The central question of this research was: how it occurs the activities of the educators training network? This question refers to reflections that are related to how knowledge is produced and the existence or non-existence of discursive marks that may indicate the share of new meanings. The results indicate that different meanings are discussed by the participants, which at times were marked by an argumentative language that made possible the development of a Creative Chain (LIBERALI, 2006). However it is necessary that the moments of creative activities are expanded. For this, the language used mainly by the educator that assumes the social role of guiding the group, needs to enable a critical reflection with confrontation between the different meanings and the construction and sharing of new meanings